Å sjå røysa som eit objekt, ein markør og ein prosess av handlingsmønster (AmS-Varia, 2020)
Cairns: graves, clearances or both, a seminar held at the Museum of Archaeology, University of Stavanger, in February 2017, attempted to look beyond the traditional concept of cairns as objects resulting from specific or single activities, focusing instead on the idea of a more fluid symbolism, constantly changing over time. This article seeks to build upon the questions and themes raised at the seminar, combining traditional definitions of cairns with the results of more recent research. The results will then be discussed in a broader, Scandinavian context. The aim is to draw attention to the idea that cairns are the product of various ongoing processes, both active and symbolic, and that these processes continuously redefine the relevance and meaning of cairns to society. The article will also draw attention to the results of more recent research and the implications they have for the field of cultural heritage management, both administratively and practically, and cultural heritage legislation in general in Norway.